The Recent Incorporation of EE Features into the Modernized Form of RP: Reasons, Conclusions and Suggestions - Haifa Adnan Salman (PROSPECTIVE RESEARCHES, 2023)
RP is an evolutionary type of pronunciation that requires coping with by its learners. It is obvious that it has witnessed many changes, and one needs only compare the so called "conservative" type of the 40s and 50s of the last century with the more "modernized" one. The mass media and the great improvement of communication during the last score rendered many forms of pronunciation available, and this includes the RP accent. Through these media it has been easy for a keen listener to perceive radical changes in some phoneme realizations and vowel qualities in the speech of many native speakers of the accent. For instance, an Iraqi learner of the RP type of pronunciation, who expects to hear /nju:z/ for news; /pleɪ/ for play; /gәʊt/ for goat, will be surprised to hear the following pronunciations, instead: /nu:z/, /plΛɪ/, /gΛʊt/. Such pronunciations, which were typical of certain regional accents, have recently found their way into the speech of many native speakers of RP. Since pronunciation is one of the most fleeting aspects of linguistic development, any recent changes in that aspect should not be overlooked by an EFL teacher or learner, for they may pave the way for a more modernized version of the accent adopted as a standard.